Sistem DC Microgrid Berbasis PLTS dan Baterai - Mulyana, Akhbar Candra; Pramana, Putu Agus Aditya; Sriyono (Politeknik Negeri Malang, 2025)
Renewable energy in microgrid systems naturally uses direct current (DC) voltage sources such as solar, hydrogen, fuel cells and wind. On the other hand, electronic device technology is also increasingly developed with the emergence of devices based on DC voltage sources. However, integration between DC voltage sources and DC electronic equipment has not been widely developed in Indonesia. Based on these problems, research will be conducted on the implementation of the DC microgrid system. The methodology of this research is to create a minimum DC microgrid system consisting of photovoltaic (PV), solar charge controller (SCC), battery and dummy load which are integrated and tested using two test scenarios. During the test, the characteristics of voltage, power flow, and battery charge discharge process were observed against load variation. The results showed that under low-load conditions, mutual charging occurred between batteries connected in parallel. When the PV power exceeds the load power, the load is supplied by the PV but when the PV power is less than the load power, the load is supplied by the PV and battery. The contribution of power flow to the load is determined by the PV supply capacity, battery voltage, and impedance. The state of charge (SOC) of a battery cannot be used as a representation of the battery voltage when the circuit is closed circuit. These findings highlight the importance of impedance and PV capacity management in DC microgrid design and support further development of efficient and resilient DC based energy systems in Indonesia.